The Effect Of The Implementation Of E-Samsat And Progressive Taxes On Motor Vehicles Tax Revenue In Sumedang District - Sri Rizki Gumilang; Maman Nurochman; Lilis Kartika (Journal of Business, Accounting and Finance, 2019)
This study aims to determine the effect of the application of e-samsat and progressive tax on motor vehicle tax revenue receipts at Samsat Sumedang Regency. This type of research method is quantitative with primary and secondary data sources. The sample collection technique in this study is probability sampling with a total of 100 samples with data collection techniques obtained from the results of questionnaires (google form) and literature study. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that the application of e- samsat has a positive and significant effect on motor vehicle tax revenue partially with a tcount value of 2.282 > ttable 1.984 while the application of progressive taxes has a significant effect on motor vehicle tax revenue receipts partially with a value of tcount 8.173 > ttable 1.984. And simultaneously the variable implementation of e-samsat and progressive tax has a significant effect on motor vehicle tax revenues with Fcount 49.599 > Ftable 3.09 and gives an effect of 50.6%.